Enclosing a target by nonholonomic mobile robots with bearing-only measurements - Zheng, Ronghao; Liu, Yunhui; Sun, Dong (Automatica (Oxford), 2015)
This paper addresses the problem of steering a single or a group of autonomous nonholonomic mobile robots to enclose a target of interest. We develop control schemes which require only local bearing measurements, and deal with encirclement of two types of targets: point target and disk target. When a single robot is used, circumnavigation schemes are proposed to achieve effective encirclement of the target. It is shown that under the proposed control schemes, the robot can circle the target from a prescribed distance without distance measurement. When multiple robots are deployed, the control schemes developed for single robot are modified by introducing a coordination mechanism, which drives the robots to distribute evenly around the target. We further discuss a control scheme that moves the robots to form a static circular formation around the target based on feedback linearization. All the proposed control schemes are validated in experiments on a group of two-wheeled differential drive mobile robots.